ID 281 – Impact and added value of electrodiagnosis in neuromuscular disorders. Issue 3 (March 2016) - Pugdahl, K.; Johnsen, B.; Qerama, E.; Beniczky, S.; Wanscher, B.; Benedek, K.; Ballegaard, M.; Dornonville de la Cour, C.; Terney, D.; Sønderborg, J.; Fuglsang-Frederiksen, A.
Abstract : Objective: To evaluate the added value of the electrodiagnostic examination (EDX) on the clinical diagnosis. Methods: Electrodiagnostic and clinical findings from 482 patients collected randomly from five Danish centers were entered in a web database and peer-reviewed electronically and at face-to-face meetings by neurophysiologists. The diagnosis reached by consensus was considered gold standard and compared with the referral diagnosis in diagnostic sub-groups: motor neurone disorders (46 patients), polyneuropathies (132), myopathies (15), root lesions (25), plexus lesions (44), neuromuscular transmission disorders (12), and upper and lower limb entrapments (150 and.58 patients). Results: EDX confirmed the referral diagnosis in 188 (39%), excluded it in 218 (45%), and changed it in 49 (10%) of the patients. In the remaining 27 (6%) the referral diagnosis was possibly confirmed. In the different diagnostic sub-groups the referral diagnosis was most often confirmed in upper limb entrapments (51%) and polyneuropathies (49%), most often excluded in myopathies (80%) and root lesions (72%), and most often changed in plexus lesions (25%) and lower limb entrapments (22%). Conclusions: EDX changes or excludes the clinical working diagnosis in more than half of the patients, which may have significant impact on management. Key message: EDX adds valuable information to the clinical diagnosis.